Hydrogen Gas Sensors Based On Nanosrystalline SnO2 Thin Films Grown On Different Substrates Using Sol-Gel Spin Coating Method - Kadhim, Imad Hussein (2017)
Sol–gel spin coating is a low-temperature method (below 100 oC) and possibly the lowest cost method for growing nanocrystalline (NC) tin dioxide (SnO2) on various substrates. NC SnO2 has potential to improve the properties of gas sensor device while also significantly lowering the cost. As-deposited and annealed SnO2 thin films suffered from cracks that appeared on the surface of the SnO2 thin films and they exhibited negative response effects of device performance. Therefore, different volume ratios of glycerin (0:1, 1:12 and 1:8) are added to the sol solutions to overcome the problem of cracks.